2015
DOI: 10.1097/md.0000000000001960
|View full text |Cite
|
Sign up to set email alerts
|

End Stage Renal Disease as a Potential Risk Factor for Retinal Vein Occlusion

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…The association between renal dysfunction and RVO has been explored previously in only 4 population-based cohort studies. 25 28 Our report was consistent with the Beaver Dam Eye Study, which reported that higher serum creatinine levels (>1.4 mg/dL) were associated with the development of RVO in a 15-year follow-up period. 26 In addition, the Hisayama study disclosed that chronic kidney disease, defined as the presence of proteinuria with an estimated glomerular filtration rate (eGFR) <60 mL/min/1.73 m 2 , increased the risk of RVO development.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The association between renal dysfunction and RVO has been explored previously in only 4 population-based cohort studies. 25 28 Our report was consistent with the Beaver Dam Eye Study, which reported that higher serum creatinine levels (>1.4 mg/dL) were associated with the development of RVO in a 15-year follow-up period. 26 In addition, the Hisayama study disclosed that chronic kidney disease, defined as the presence of proteinuria with an estimated glomerular filtration rate (eGFR) <60 mL/min/1.73 m 2 , increased the risk of RVO development.…”
Section: Discussionsupporting
confidence: 88%
“…A few previous studies have discussed the association between ESRD and RVO, but the results of published studies were limited by the small number of patients or the absence of comparative control data. 25 28 Using a nationwide population-based dataset, we designed a cohort study to investigate the risk of RVO following ESRD in Taiwan.…”
Section: Introductionmentioning
confidence: 99%
“…Our study has the longest follow-up period (mean, 7.37 years) and, to the best of our knowledge, is the first to examine the association between ESRD and RVO using an extensive database in South Korea. Chen et al 18 and Chang et al 19 reported the adjusted HR for RVO development in ESRD patients as 1.50 (95% CI, 1.13-1.99; P ¼ 0.0056) and 3.05 (95% CI, 2.64-3.51; P < 0.05),…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, only in Taiwan were there longitudinal epidemiologic studies with extensive data evaluating the association between ESRD and RVO. 18,19 As an epidemiologic study, confirming reproducibility is a crucial aspect. In addition, South Korea and Taiwan are the only countries in East Asia in which a nationwide cohort database is established for the entire nation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation